2022
DOI: 10.3389/fspor.2021.769031
|View full text |Cite
|
Sign up to set email alerts
|

Becoming InterActive for Life: Mobilizing Relational Knowledge for Physical Educators

Abstract: The overarching purpose of the InterActive for Life (IA4L) project is to mobilize relational knowledge of partnered movement practices for physical education practitioners. Through a participatory, motion-sensing phenomenological methodology, relational knowledge gleaned from world class experts in salsa dance, equestrian arts, push hands Tai Chi and acroyoga, and analyzed through the Function2Flow conceptual model, was shared with Physical Education Teacher Education (PETE) students. They, in turn, made sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We encourage the uptake of flow theory for future PL research and approaches to assessment with the caveat that, rather than sequestering flow to an elitist “zone” of high performance, we recommend educative and progressive ways in which kinaesthetic feelings and synergistic micro-flows can be cultivated [i.e. ( 93 , 94 , 105 ),] no matter what the level of competency.…”
Section: Physical Literacy Social Participation and Interactive Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…We encourage the uptake of flow theory for future PL research and approaches to assessment with the caveat that, rather than sequestering flow to an elitist “zone” of high performance, we recommend educative and progressive ways in which kinaesthetic feelings and synergistic micro-flows can be cultivated [i.e. ( 93 , 94 , 105 ),] no matter what the level of competency.…”
Section: Physical Literacy Social Participation and Interactive Flowmentioning
confidence: 99%
“…If we are to radically shift the declining rates of physical activity in the adult and older adult populations (80), it seems we would be advised to again emphasize this love of movement. In doing so, we mean not merely the fun and satisfaction of moving competently and with confidence, but the joy and aliveness inherent to moving functionally, in good form, and with kinesthetic feeling and energetic flow (92)(93)(94). Embracing such a love of moment in a conceptually defensible way means, however, finding its validation in the ongoing articulation of PL.…”
Section: Physically Literate For Lifementioning
confidence: 99%
“…We are thus moved not only to experience partnered practices for the pleasures individually derived but also to further kinetic, aesthetic, kinesthetic, and energetic ways of moving joyfully with others. Over the past 5 years, within our Social Sciences and Humanities Research Council-funded multiphase InterActive for Life (IA4L) project, we have observed, interviewed, and made video documentaries of expert practitioners of partnered movement practices ranging from Push-Hands Tai Chi, to AcroYoga, Salsa Dance, and Equestrian Arts (Phase 1); mobilized our findings to enhance pedagogical practices of Teacher Education students through the co-creation of generalized partnered activities and resources (Phase 2); and responded to emerging and seasoned educators with vested interest in prioritizing motile communication and relational connectedness in their pedagogical practices (Phase 3); Lloyd, 2021;Lloyd & Smith, 2021, 2022a, 2022bNyetap et al, 2020;Smith & Lloyd, 2022).…”
Section: Reflexive Motional Inquirymentioning
confidence: 99%
“…No instructor ever took the ball away and invited students to explore the dynamic dance of postural and positional weight transfers in offensive and defensive play. As somatically oriented educators such as Sondra Fraleigh (2015) recommend, we have s-l-o-w-e-d down to help these student teachers feel the profound vitality affects (Sheets-Johnstone, 2011) of something as simple as a forward lean when facing a partner (Lloyd & Smith, 2022a) in a variety of lead-follow games that they have co-created (i.e., Leaning in Mirror Walk; Nyetap et al, 2020;Lloyd & Smith, 2022b;Smith & Lloyd, 2022).…”
Section: Reflexive Motional Inquirymentioning
confidence: 99%
See 1 more Smart Citation